Understand the Programmers Mindset for Beginners - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn some counter-intuitive ways to think about programming as a beginner. It is ok to feel stupid, it means you are on the right path! Topics include: * Failure is good * The goal of programming is to reduce complexity * Automation is a requirement * Continuously Improve your code * Embrace Automation and Monitoring.